CCDC85A is regulated by miR-224-3p and augments cancer cell resistance to endoplasmic reticulum stress - Takahashi, So; Takagane, Kurara; Itoh, Go; Kuriyama, Sei; Umakoshi, Michinobu; Goto, Akiteru; Yanagihara, Kazuyoshi; Yashiro, Masakazu; Iijima, Katsunori; Tanaka, Masamitsu (Frontiers in Oncology, 2023)
MicroRNAs (miRNAs) play pivotal roles in the tumor microenvironment. Here, we analyzed miRNAs in tumor stromal fibroblasts. Expression of miR-224-3p in cancer-associated fibroblasts (CAF) from scirrhous gastric cancer patients was lower than in normal fibroblasts (NF). Introduction of a miR-224-3p mimic attenuated migration and invasion of CAF. Coiled-coil domain containing 85A (CCDC85A), whose function in tumors is not understood, was the target gene of miR-224-3p. Immunohistological analysis revealed that CCDC85A is expressed to varying degrees by cancer cells and CAFs in gastric and pancreatic carcinomas. Downregulation of CCDC85A in cancer cells revealed that these cells are vulnerable to endoplasmic reticulum (ER) stress induced by thapsigargin or tunicamycin, which were ameliorated after addback of CCDC85A. Injection of NF-derived exosomes containing miR-224-3p into the xenograft tumor increased tumor shrinkage by cisplatin treatment. Mechanistically, CCDC85A associated with the molecular chaperone GRP78 and GRP94, thereby inhibiting association of these negative regulators of the unfolded protein response (UPR), leading to sustained activation of PERK and downstream eIF2〈 and ATF4 upon ER stress. These data suggest a novel miR-224-3p-mediated function for CCDC85A: protection from ER stress and cisplatin resistance.